Strategia zarządzania wiedzą czy strategia wiedzy? - Stańczyk-Hugiet, Ewa (Knowledge management strategy or knowledge strategy, 2006)
The aim of presented paper is to clarifying and explaining meaning of such categories as knowledge strategy, knowledge management strategy and knowledge management system. Knowledge management system consist of three levels: identification in terms of knowledge strategy, implementation i.e. knowledge processes and operational - knowledge management's tools.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 214-220